Improving Transparency and Accountability in Public-Private Partnerships : Disclosure Diagnostic Report - Islamic Republic of Afghanistan - World Bank (World Bank, Washington, DC, 2021)
In May 2016, the World Bank published a Framework for Disclosure of Information in Public-Private Partnerships (PPPs), which provides a template for the preparation of a PPP Disclosure Diagnostic that assesses the transparency and accountability of PPP programs based on the disclosure of information. Between March 2020 and October 2020, a joint Government of the Islamic Republic of Afghanistan and World Bank team conducted a study on PPP disclosure in Afghanistan, using the World Bank’s PPP Disclosure Diagnostic template. This study led to the preparation of a PPP Disclosure Diagnostic Report (hereinafter ‘Diagnostic Report’) for Afghanistan. The Diagnostic Report examines the political, legal, and institutional environment for the disclosure of information on PPPs in Afghanistan. Based on these findings, benchmarked against the World Bank’s disclosure framework, the Diagnostic Report provides a gap assessment of the environment for PPP disclosure in Afghanistan. It makes specific recommendations to improve disclosure, including recommended customized guidelines for PPP disclosure in Afghanistan. The findings suggest that there has been some movement toward greater transparency and openness in all areas of government in Afghanistan, but that there is still scope for further progress given that relevant legal reforms are relatively new and still to be fully institutionalized. Article 50 of the 2004 Constitution of Afghanistan ensures that citizens ‘have the right of access to information’ from public institutions. This principle was enhanced substantially with the enactment of the Access to Information Law in 2014, which was subsequently revised in 2019.2 The law further guarantees access to information and aims to ‘ensure transparency, strengthen the culture of provision of information, promote people’s participation in good governance, ensure accountability in the conduct of institutions, and combat corruption’.